Asian American religious cultures - Lee, Jonathan H. X.; Matsuoka, Fumitaka; Yee, Edmond, 1938-; Nakasone, Ronald Y. (Santa Barbara : ABC-CLIO, 2015)
Despite constituting a fairly small proportion of the U.S. population - roughly 5 percent - Asian Americans are a widely diverse group with equally heterogeneous religious beliefs and traditions. This encyclopedia provides a single source for authoritative information on the Asian American and Pacific Islander religious experience, addressing South Asian Americans, such as Indian Americans and Pakistani Americans; East Asian Americans, including Chinese Americans, Japanese Americans, and Korean Americans; and Southeast Asian Americans, whose ethnicities include Filipino Americans, Thai Americans, and Vietnamese Americans. Pacific Islanders include Hawaiians, Samoans, Marshallese, Tongan, and Chamorro. The coverage includes not only traditional eastern belief systems and traditions such as Buddhism, Confucianism, and Hinduism as well as Micronesian and Polynesian religious traditions in the United States, but also the culture and religious rituals of Asian American Christians.
Volume 1. Essays and A-H -- volume 2. Entries I-Z.
Includes bibliographical references (pages 993-1009) and index.
Keywords: Asian Americans -- Religion -- Encyclopedias; Asian Americans -- Social life and customs -- Encyclopedias; United States -- Religion -- Encyclopedias